PENCARIAN NILAI KESALAHAN RELATIF DAN LITERATUR UNTUK PRAKTIKUM BANDUL MATEMATIS PADA PRAKTIKUM FISIKA DASAR STMIK JAKARTA STI&K DENGAN APLIKASI BAHASA C - Intan Kusuma Dewi; Melani Dewi Lusita, Skom, MMSI Melani Dewi Lusita, Skom, MMSI (Jurnal Sistem Informasi, 2007)
In writing this study, the authors try to explain how to find the value of an error inan experiment conducted by the lab in the Physics Laboratory of the moduleentitled Basic Mathematical Pendulum.Here the author was asked to run a practice in Basic Physics Laboratory to obtainan accurate observation data and the data was processed with the formulas thatalready exist in order to find the value of relative error and literature from manualto computerized ways.